What microsurgeon, orthopaedic and plastic surgeon should know about bionic hand. (December 2019) - Bumbaširević, Marko; Lešić, Aleksandar; Palibrk, Tomislav; Georgescu, Alexandru Valentin; Matei, Ileana Rodica; Vučetić, Čedomir; Pierluigi, Tos; Matić, Sladjana; Damjanović, Dušan; Raspopović, Staniša
Abstract: Hand loss is a catastrophic event that generates significant demands for orthopedics and prosthetics. In the course of history, prostheses evolved from passive esthetic replacements to sophisticated robotic hands. Yet, their actuation and particularly, their capacity to provide patients with sensations, remain an unsolved problem. Sensations associated with the hand, such as touch, pain, pressure and temperature detection are very important, since they enable humans to gather information from the environment. Recently, through a synergistic multidisciplinary effort, medical doctors and engineers have attempted to address these issues by developing bionic limbs. The aim of the bionic hands is to replace the amputated hands while restoring sensation and reintroducing hand-motor control. Recently, several different approaches have been made to interface this sophisticated prosthesis with residual neuro-muscular structures. Different types of implants, such as intramuscular, epineural and intraneural, each have their own complementary advantages and disadvantages, which are discussed in this paper. After initial trials with percutaneous leads, present research is aimed at making long-term implantable electrodes that give rich, natural feedback and allow for effortless control. Finally, a pivotal part in the development of this technology is the surgical technique which will be described in this paper. The surgeons' insights into this procedure are given. These kinds of prostheses compared with the classic one, hold a promise of dramatic health and quality of life increase, together with the decrease the rejection rate.